2008
DOI: 10.1111/j.1538-7836.2008.02991.x
|View full text |Cite
|
Sign up to set email alerts
|

Covalent regulation of ULVWF string formation and elongation on endothelial cells under flow conditions

Abstract: Summary. Background and Objectives: The adhesion ligand von Willebrand factor (VWF) is a multimeric glycoprotein that mediates platelet adhesion to exposed subendothelium. On endothelial cells, freshly released ultra-large (UL) VWF multimers form long string-like structures to which platelets adhere. Methods: The formation and elongation of ULVWF strings were studied in the presence of the thiol-blocking Nethylmaleimide (NEM). The presence of thiols in ULVWF and plasma VWF multimers was determined by maleimide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
71
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 42 publications
3
71
0
1
Order By: Relevance
“…40 At very high levels of shear stress, VWF multimers can form a network of multistranded bundles on a collagen matrix 36 or aggregate irreversibly in solution, 41 possibly by forming new intersubunit disulfide bonds. 42,43 At levels of fluid shear stress too low to induce VWF self-association on other surfaces 36,40 or in solution, 41,42 we have observed that acutely secreted VWF molecules self-associate in diverse patterns, forming twisted bundles and networks on endothelial cells ( Figure 2). These multistranded structures may enhance the stability of VWF molecules on endothelial surfaces and probably account for the extreme length of some VWF strings.…”
Section: Discussionmentioning
confidence: 93%
“…40 At very high levels of shear stress, VWF multimers can form a network of multistranded bundles on a collagen matrix 36 or aggregate irreversibly in solution, 41 possibly by forming new intersubunit disulfide bonds. 42,43 At levels of fluid shear stress too low to induce VWF self-association on other surfaces 36,40 or in solution, 41,42 we have observed that acutely secreted VWF molecules self-associate in diverse patterns, forming twisted bundles and networks on endothelial cells ( Figure 2). These multistranded structures may enhance the stability of VWF molecules on endothelial surfaces and probably account for the extreme length of some VWF strings.…”
Section: Discussionmentioning
confidence: 93%
“…Self-association has been reported to be covalent and involve unpaired cysteine residues. 12,14 Considering the cluster of potential free thiols in and around the C2 domain, 12,13 we focused on identifying the particular cysteines involved in this region and understanding how they exchange between VWF molecules during lateral self-association.…”
Section: Discussionmentioning
confidence: 99%
“…14 Mature VWF, both purified from plasma and made recombinantly, contains unpaired cysteine thiols 12,[15][16][17] that have been localized to the N-terminal D3 and C-terminal C domains. 12,13,17 Presumably, one or more of these cysteine thiols is involved in VWF self-association.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with the aforementioned calculations, these organelles should release strings no longer than approximately 19 m. Our data show that FVIII-expressing endothelial cells release strings that are much longer, with an average length of 340 m ( Figure 7A). This argues in favor of linkage of VWF multimers after release 44,45 or pooling of WPB content during multigranular exocytosis. 28 Moreover, tubular organization of VWF appears dispensable for the formation of UL-VWF string on the surface of endothelial cells.…”
mentioning
confidence: 98%